Digital competence of higher education professors in the adequation of remote teaching - Piontkewicz, Regiane (2023)
Introduction: Adoption of remote teaching for the continuation of face-to-face classes during COVID-19 pandemic, urgently required the development of digital competences by academic community. Objective: analyze the digital competence of Brazilian higher education professors during the period of adaptation to remote teaching. Method: it is a survey with 322 Brazilian higher education professors. A questionnaire was applied to raise the professors’ perception about remote teaching, as well as to assess their digital competence. Results: digital competences that need to be better developed by professors are: adoption of information management strategies; development of tools for online assessments; and use of tools to promote gamification and collaborative learning. Discussion: the development of these digital competences helps in solving the problems with remote teaching. Professors who usually take courses and exchange experiences are the ones with a greater development of the analyzed digital skills.